The Theories of Interconstitutionality and Transconstitutionalism. Preliminary Insights from a Jus-cultural Perspective (With a view to Transnational Social Justice) - Vale, Luís A. Malheiro Meneses do (2015)
In the following pages, some light will hopefully be shed into the recent proposals of interconstitutionality and transconstitutionalism – deemed highly influential among Portuguese and Spanish-speaking countries – considering them against the backdrop defined by the more general disquisitions recently devoted to interculturality and transculturality in their quality of practical responses to the globalization and social differentiation phenomena. Acknowledging the fact that, even inside the juridical linguistic game and within the juristic community of interpreters, the new narratives interwoven through the above mentioned concepts are becoming more and more intricate – v.g., including epistemic and normative, as well as subjective and objective perspectives, giving birth to new elaborate semantic networks and covering an ever growing territory – it is important to admonish, at the outset, that, in this stance, we cannot but provide a preliminary and provisory map of the vast continent thereby comprised. As a consequence, the present text will limit itself to the signalling of some landmarks and the rough drawing of the basic lineaments for further (and certainly wiser and more competent) cartographic and exploratory endeavours.